Digital fluency : understanding the basics of artificial intelligence, blockchain technology, quantum computing, and their applications for digital transformation - Lang, Volker, 1981- (Apress, 2021)
If you are curious about the basics of artificial intelligence, blockchain technology, and quantum computing as key enablers for digital transformation, Digital Fluency is your handy guide. The real-world applications of these cutting-edge technologies are expanding rapidly, and your daily life will continue to be affected by each of them. There is no better time than now to get started and become digitally fluent. You need not have previous knowledge of these technologies, as author Volker Lang will expertly guide you through this digital age. He illustrates key concepts and applications in numerous examples and figures throughout Digital Fluency, and the end of each chapter presents you with a helpful implementation checklist of central lessons before proceeding to the next. This book gets to the heart of digital buzzwords and concepts, and tells you what they truly mean. Breaking down topics such as AI-powered automated driving, blockchain-based cryptocurrencies, quantum optimization of urban traffic, and more is imperative to being ready for what the future of industry holds. Whether your own digital transformation journey takes place within your organization, your studies, or your individual household, Digital Fluency maps out a concrete digital action plan for all of your technology and strategy needs.